Risk factors and quality of life in adults with dysphagia after posterior skull base surgery: a cross-sectional study - Wang, Qiao; Cheng, Shang-Jin; Duan, Dan; Cui, Wen-Yao; Liu, Wen-Jie (Frontiers in Oncology, 2025)
IntroductionThe study aimed to evaluate the current status of swallowing function and quality of life in patients undergoing posterior skull base surgery, identify risk factors for dysphagia, and provide evidence for early interventions.MethodPatients undergoing posterior skull base surgery were prospectively enrolled, from June 2023 to June 2024. Data collection included demographics, disease-related details, swallowing function assessment, and scores of Swallowing-Quality of Life (SWAL-QOL). The logistic regression was used to identify risk factors influencing dysphagia, while the SWAL-QOL questionnaire was used to investigate the quality of life in patients undergoing posterior skull base surgery.ResultsAmong the 143 patients, approximately 50% developed postoperative dysphagia. Logistic regression analysis identified a history of choking, surgical duration, and the total score of nutritional risk as independent predictors of dysphagia. The area under the Receiver Operating Characteristic Curve was 0.797 (95%CI: 0.722–0.871). The SWAL-QOL questionnaire revealed significantly lower scores across all dimensions in patients with dysphagia (P < 0.05), particularly in swallowing function, eating duration, and food selection.ConclusionPostoperative dysphagia is prevalent after posterior skull base surgery and significantly impairs quality of life. Routine screening and proactive management of swallowing function are essential for improving clinical outcomes and enhancing swallowing-related quality of life.